Phytostabilization of multi-metal contaminated mine waste materials: long-term monitoring of influence of soil amendments on soil properties, plants, and biota and the avoidance response of earthworms - Gudichuttu, Vindhya (Kansas State University, 2013)
Mine waste materials from the Tri-State mining region in Kansas, Missouri, and Oklahoma pose environmental hazards. The area is contaminated with trace elements, such as Pb, Zn and Cd, which are transported to surrounding areas through water, wind erosion, and runoff. Phytostabilization or establishing healthy vegetative cover could be used to reduce or control these contaminated materials from further spreading with wind and water. However, further research is needed to monitor the long-term sustainability and assess if high applications of compost amendments could help to facilitate soil reclamation. The overall focus of this thesis was to monitor long-term effects of compost or lime additions at two different rates, with or without other soil amendments, on soil properties, plants, and soil biota. We used the earthworm avoidance test as a screening tool for testing effects of soil amendments on ecotoxicity. In the first field study, pelletized manure compost additions of 448 Mg ha⁻¹ significantly decreased the bioavailable Pb, Zn, and Cd while increasing plant nutrients, vegetative cover, and plant biomass as compared to the contaminated control and the low addition of compost (224 Mg ha⁻¹) over 2.5 years. Plant tissue metal concentrations with compost addition did not show any phytotoxicity in this study. Lime additions did not show any significant effect on any of the measurements. Results from the first study suggest that one time addition of large quantities of compost at 224 to 448 Mg ha⁻¹ can support establishing and maintaining healthy vegetative cover at least for a 2.5 year period. In the second field study, long-term monitoring of the effectiveness of the amendments was studied. Compost was applied at two different rates (45 or 269 Mg ha⁻¹) in 2006. Various chemical properties, microbial activities, and vegetative growth or plant biomass were measured approximately for 4.5 years to evaluate long-term changes in soil quality and sustainability of phytostabilization efforts, when combined or assisted with soil amendments to improve the quality of trace element-contaminated mine waste materials. Plants grown with compost additions of 269 Mg ha⁻¹ showed higher nutrients, biomass, and enzyme activities as compared to plants grown on the contaminated control and with the low addition of compost (45 Mg ha⁻¹) over 4.5 years. Decrease in plant biomass and enzyme activities seen in the high compost treatments by the end of the study period suggested that long-term sustainability of these efforts may require repeated addition of soil amendments every 4 to 5 years. Additionally, a laboratory study was conducted to assess the long-term effects of treatments used in the second field study on ecotoxicity using the avoidance behavior responses of the earthworm Eisenia fetida. There was no mortality of earthworms after a 48 h exposure period of any of these treated and untreated mine waste materials. Avoidance was clear for the contaminated control and the low compost treatment (45 Mg ha⁻¹). Moreover, the contaminated control did show habitat limitation (< 20% of earthworms was found in test soil). Current research studies provide evidence that, high rates of compost applications can be used to stabilize and reduce the bioavailability of trace elements in mine waste materials.
Keywords: Mine wastes; Compost; Phytostabilization; Earthworm avoidance test; Agronomy (0285)